Research of the thermal desorption processes in oxide mixtures at laser effect - Katrechko, V.V.; Vinnikov, D.V.; Yuferov, V.B.; Ilichova, V.O.; Svichkar, A.S.; Buravilov, I.V.; Timofeev, V.D.; Bobrov, O.G. (Вопросы атомной науки и техники, 2020)
To investigate the physical-chemical processes occurring during the heating stage of spent nuclear fuel magneto plasma reprocessing a study of thermal desorption of oxides and oxide mixtures as SNF simulators under the influence of stationary laser radiation are being studied. Preliminary experiments were carried out. X-ray diffraction and energy dispersive X-ray microanalysis of the film deposited on the substrate after laser influence on a mixture of B₂O₃/ZrO₂ oxides have been performed.